The poetic purpose and its effect on producing the meaning in the Iraqi poetry of the 1950: Abdel Wahab Al-Bayati as a model - Hamid Abdullah, Raghad (Al-Adab Journal, 2021)
The generation of the fifties carried different intellectual and artistic visions from the previous generations، by virtue of the developments witnessed by the Arab nation in general and Iraq in particular، which were evoked by what the Iraqi reality witnessed at all political، social and economic levels that led to the development of intellectual awareness in the various events it carried. Among the poets of that period، and then one of its outputs was the emergence of poetic objects and themes that reflected to the recipient that reality with various meanings according to the poetic theme So our research came to find out some of those poetic purposes to show their effect in producing meaning for the recipient in that period of time، and we chose the poet Abdul Wahhab Al-Bayati to be a model for the study.